Efficacy, Safety and Patient-Reported Outcomes with Preservative-Free (PF) Tafluprost or PF-Dorzolamide/Timolol Compared with Preserved Latanoprost: A Prospective Multicenter Study in Korean Glaucoma Patients with Ocular Surface Disease - Sang-Woo Park; Jiwoong Lee; Michael S. Kook (MDPI AG, 2022)
To compare the efficacy, patient-reported satisfaction, and safety of preservative-free (PF)-tafluprost, PF-dorzolamide/timolol and preservative-containing (P)-latanoprost in Korean glaucoma patients with ocular surface disease (OSD). In a multicenter, prospective, interventional, non-randomized, controlled 12-week trial, 107 eligible patients received PF-tafluprost (n = 37), PF-dorzolamide/timolol (n = 34), or P-latanoprost eye drops (n = 36). Outcomes included changes from baseline in OSD Index (OSDI) scores (primary endpoint), intraocular pressure (IOP), and patient-reported treatment satisfaction, and safety at 12 weeks. At 12 weeks, the mean total OSDI and subdomain (dry eye symptoms, visual-related function, environmental triggers) scores significantly improved from baseline with PF-tafluprost and PF-dorzolamide/timolol, but not with P-latanoprost. Significantly more PF-tafluprost than P-latanoprost recipients reported 'highly improved/improved' satisfaction (no significant difference between PF-dorzolamide/timolol and P-latanoprost). IOP changes were comparable among all three treatment groups. No new safety concerns were observed. PF-tafluprost and PF-dorzolamide/timolol showed statistically and clinically significant reductions in OSDI compared with P-latanoprost in Korean glaucoma patients with OSD.